The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1182/blood-2007-01-067579
|View full text |Cite
|
Sign up to set email alerts
|

In vivo p53 response and immune reaction underlie highly effective low-dose radiotherapy in follicular lymphoma

Abstract: Very low-dose irradiation (2 ؋ 2 Gy) is a new, effective, and safe local treatment for follicular lymphoma. To understand the biologic mechanisms of this extremely effective response, we compared by microarray the gene-expression profile of patients' biopsies taken before and after radiation. In all patients, a major and consistent induction of p53 target genes was seen. p53 targets involved in cellcycle arrest and apoptosis showed the same mode of regulation, indicating that, in vivo, both are activated simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 24 publications
3
46
0
1
Order By: Relevance
“…Although TP53 mutation is more frequent in older patients, 4 of 12 mutated cases here were younger than 60 years, and nonmyeloablative allogeneic stem cell transplantation may be an option. Radiotherapy would not be predicted to prolong responses, 25 as the majority of mutations observed here were nonfunctional (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…Although TP53 mutation is more frequent in older patients, 4 of 12 mutated cases here were younger than 60 years, and nonmyeloablative allogeneic stem cell transplantation may be an option. Radiotherapy would not be predicted to prolong responses, 25 as the majority of mutations observed here were nonfunctional (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…the list of discriminating genes included ptgs1, cFB, Anpep, cXcr4, ZAp70, Il8, VAV1, IcAM1, cD59, cAsp1, tp73, BrcA1, cDc25A, rAD51 and tgFB2. In 2007, Knoops et al firstly reported irradiation-induced genes related to macrophage activation and immune response in follicular lymphoma patients (37). According to analysis of the complement and coagulation cascades pathway, previous studies have linked malignant transformation, tumor angiogenesis and metastasis to the generation of clotting intermediates (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Total body radiation with 2 Gy or 2 3 2 Gy leads to a .80% response rate in indolent non-Hodgkin lymphoma, with local tumor control for .2 y (9, 10). This radiation dose is expected to be less damaging for tumor cells than high doses, although treatment-related p53-mediated proliferation arrest and apoptosis of follicular lymphoma cells have been reported (11). Low-dose total body, but not localized, radiation of the tumor with 0.2 Gy induced T cell activation and decreased the incidence rate of metastasis in a preclinical tumor model, suggesting broad immune effects (12).…”
mentioning
confidence: 99%
“…RT has two well-known immunological links, as follows: one is the need for properly functioning host cellular immune system, especially CD8 + T cells, for maximum benefit from RT (1,2); the second is the much discussed abscopal effect (regression of distant disease following local irradiation) that, in preclinical models (3,4), was proved to be immune mediated. Generally, tumors are treated with a single high dose (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Gy) or multiple fractions of ∼2 Gy radiation, amounting to 60-70 Gy total dose. High-dose RT can provide tumor Ags from dying cells for dendritic cells that then cross-present them to CD8 + T cells.…”
mentioning
confidence: 99%